Quality of hospital and follow-up care among patients with type 2 diabetes and newly diagnosed cardiovascular disease: a cohort study in Sweden - Junmei Miao Jonasson; Björn Agvall (BMJ Open)
Objective To examine hospital discharge practices, including clinical and laboratory assessments, in patients with type 2 diabetes mellitus (T2DM) following their first hospitalisation for cardiovascular disease (CVD), and to explore the association of these practices with adverse events, defined as hospital readmission, emergency department visits and mortality.Design Retrospective cohort study.Setting Follow-up for 100 days after a newly diagnosed CVD among patients with T2DM in Region Halland, Sweden.Participant A total of 1482 patients with T2DM and a new diagnosis of CVD during hospitalisation were included. Patients were followed from hospital discharge for up to 100 days. Inclusion criteria were a hospital discharge diagnosis of CVD and a prior diagnosis of T2DM. Patients with incomplete discharge data or without follow-up records were excluded.Primary and secondary outcome measures The primary outcome was the overall risk of serious adverse events after hospital discharge, including mortality, hospital readmission and ED encounters, within 100 days of discharge. Secondary outcomes included primary care visits and pharmacotherapy adjustments for CVD and T2DM during the same period.Results The readmission rate within the study period was 27%, while 86% of patients visited primary care within 100 days after discharge. Cardiovascular pharmacotherapy increased, with beta-blocker usage rising to 73% and statin use reaching 82%. A significant, though modest, increase in pharmacotherapy for T2DM was observed, with metformin use increasing from 53% to 57% (p<0.001). Laboratory test results and clinical measurements at discharge, including missing glycated haemoglobin values (68%) and elevated systolic blood pressures, were associated with modest treatment adjustments at discharge, suggesting potential gaps in discharge practices and documentation.Conclusions Despite moderate improvements in postdischarge pharmacotherapy, limited changes in diabetes management suggest room for optimisation. The findings emphasise the need for improved discharge planning and continuity of care. Future research should investigate the effects of standardised discharge protocols on treatment outcomes and readmission rates for this patient group.